2022
DOI: 10.1177/03000605221101329
|View full text |Cite
|
Sign up to set email alerts
|

Warthin-like mucoepidermoid carcinoma of the parotid gland: a clinicopathological analysis of two cases

Abstract: Mucoepidermoid carcinoma (MEC) is the most common malignant tumour of the salivary gland, primarily involving the parotid gland. Here, the cases of two patients, aged 47 and 67 years, respectively, who underwent surgery for pathologically confirmed Warthin-like MEC of the parotid gland between January 2019 and December 2019 in Anyang Tumour Hospital, are described. In each case, the tumour consisted of epithelial and lymphoid cell components, covered with two or more layers of epithelium, with visible scattere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Since the first report by Ishibashi et al 1 in 2015, only 28 cases ( Table 1 ) of WT-like MECs have been reported in the literature, including the present case. 1 , 2 , 5 7 , 11 , 12 , 14 18 The tumour preferentially affect females and all cases originate in the parotid gland. It is generally thought that this tumour appears in adults, but it may also occur in teenagers, as the broad age range is 13–67 years.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report by Ishibashi et al 1 in 2015, only 28 cases ( Table 1 ) of WT-like MECs have been reported in the literature, including the present case. 1 , 2 , 5 7 , 11 , 12 , 14 18 The tumour preferentially affect females and all cases originate in the parotid gland. It is generally thought that this tumour appears in adults, but it may also occur in teenagers, as the broad age range is 13–67 years.…”
Section: Discussionmentioning
confidence: 99%